Ashghal Quality Assurance & Quality Control system - QSD Role in Monitoring & Reporting the Quality Performance in Ashghal Projects - Al-Ibrahim, Aisha Abdulaziz A. M.; Al-Thani, Aisha Abdulla N. J.; Plexousaki, Effrosyni; Al-Ansari, Mounera Ismail R M (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2023)
Ashghal has established a robust system of quality control and quality assurance for all projects constructed by Ashghal. Ashghal Departments are supervising a sophisticated system of quality control and quality assurance processes and procedures, implemented by the Consultants, Contractors, and Key Supply Chain Partners of Ashghal projects (e.g., Sub-Contractors, Key Suppliers, and Independent Laboratories). This paper illustrates how Ashghal Quality & Safety Department (QSD) monitors and reports the quality performance in Ashghal constructed projects to ensure continuous improvement and adherence to Ashghal quality strategy, policy mission, and targets. QSD is operating as Third Party, reporting directly to Ashghal President, and is monitoring and reporting the compliance of the industry to the quality requirements defined in Qatar Construction Specifications (QCS, 2014), Contracts, Professional Services Agreements, ISO 9001:2015 Standard and specific Ashghal requirements. Effective root cause analysis carried out by the auditing team has led to value-adding activities. QSD has established specific Key Performance Indicators (KPIs) for the management of non-conformities and corrective actions, to improve the performance and minimize the deviations and failures of compliance. QSD is conducting focused and system audits at Ashghal projects and the supply chain and is liaising with departments and individual projects as necessary, to agree on Lessons Learned and Actions to improve the quality of works. These activities include the establishment of consistent criteria of the qualifications and experience of the quality staff of Ashghal departments and Consultants’ teams. QSD is making quarterly presentations to the Ashghal President regarding the performance of the Departments (including Contractors’ and Consultants’ performance) and of the Ashghal Project Managers. The established criteria and evaluation related to the quality are dynamic and reviewed/updated periodically to ensure the improvement of the Quality Performance of Ashghal Projects.